Effects of US Policies on the Afghan National Economy : A Quantitative Analysis - Sakthivel, Adithya Vikram (Arthshastra Indian Journal of Economics & Research, 2021)
Ever since the overthrow of the autocratic Taliban regime by the United States military and their allies in 2001 as part of the Global War on Terror and the establishment of a democratic and relatively more liberal Afghan government, the economic health of this newly formed country was dependent on the decisions taken by its superpower allies. This can be observed with the inflation rates following similar trends to that of the United States as identified by this paper. Additionally, this study identified several events and factors related to the United States affecting the Afghan macro-economic stability as a whole.